Hysteroscopic evaluation in infertility and abnormal uterine bleeding - Kaur, Navneet; Bhatia, Ruby; Kaur, Paramjit; Bhopal, Surinder K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysteroscopy an endoscopic procedure for visualization of uterine cavity may be extensively used in both primary and secondary infertility and abnormal uterine bleeding for evaluating intrauterine pathology. The objectives of this study were to visualize and identity intrauterine pathology in both primary and secondary infertility and abnormal uterine bleeding (AUB) by hysteroscopic evaluation and to perform hysteroscopic guided therapeutic procedures like endometrial currettage, polypectomy, adhesiolysis. Methods: Hysteroscopic evaluation of uterine cavity for any intrauterine pathology in AUB and Infertility. Adhesiolysis, polypectomy, endometrial biopsy misplaced copper T removal were carried out under hysteroscopic vision. Results: Intrauterine synechia in 20.51%, Submucous fibroid in 5.13%, bicornuate uterus, endometrial hyperplasia and endometrial polyp were seen in 2.56% patient each were detected in infertility group while 81.95% cases with AUB had abnormal intrauterine pathology commonest being endometrial hyperplasia in 33.33% followed by endometrial polyps in 23.81% cases, submucous fibroid and misplaced copper T in 9.52% each and intrauterine synechia in 4.76% patient. Endometrial biopsy and polypectomy was done in 23.80% each with AUB, misplaced copper T removal in 9.52% and adhesiolysis in 4.76% patient with AUB. Conclusions: Hysteroscopy remains gold standard for evaluating intrauterine lesions in abnormal uterine bleeding and infertility. A safe, simple minimally invasive procedure not only diagnostic but therapeutic modality for adhesiolysis, endometrial biopsy/curettage, polypectomy, misplaced copper T removal under direct vision with minimal complication within reach of every Gynaecologist thereby reducing burden of major surgical intervention.